INTERCULTURAL TEACHING EXPERIENCES OF A SELECTED GROUP OF FILIPINO PRE-SERVICE TEACHERS IN AN OVERSEAS PRACTICUM IMMERSION (Proceedings of the International Conference on Education, 2019)
Quality pre-service teacher training is a key part of Basic Education in the Philippines. As such, it is of great significance that the highest standards are achieved by the pre-service teachers. These standards are reflected on the seven (7) domains that represent the desired features of the teaching-learning process as stipulated in CMO 30 s. 2004.The Melbourne Declaration on Educational Goals for Young Australians (2008: p 4), cited that global integration and international mobility have increased rapidly in the past decade. As a consequence, new and exciting opportunities for Australians are emerging. This heightens the need to nurture an appreciation of and respect for social, cultural and religious diversity, and a sense of global citizenship.White and Toms (2009) stated that globalization is not entitled only to business courses, but is relevant to all courses that are qualified for higher education. Therefore, classroom instructors for all disciplines must shift their teaching philosophy from a domestic pedagogyto a global perspective. Educators must equip students with knowledge about global economics that will have a direct impact to students’ future job choices (Dowling & Welch, 2005).
Keywords: Intercultural teaching; Philippines